Investigation of Problem Solving and Perfectionism Levels of Sports High School Students - Tan, Metin; Yaşın, İsrafil and Can, Hasan Ceyhun (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
This study aimed to examine the problem-solving skills and perfectionism levels of sports high school students and to determine the relationship between them. The universe of the study consisted of 964 students studying in sports high schools in Gaziantep in the 2022-2023 academic year. The sample consisted of a total of 284 students who voluntarily agreed to participate in the study. 126 of the students included in the study were female and 158 were male. To compare the scores of the Students’ Problem-Solving Skills Perception Scale (PSPSS) and the Frost Multidimensional Perfectionism Scale (FMPS), t-test, One-Way Anova, and Pearson test were used to examine the relationship between the scale scores. As a result of the study, it was determined that the problem-solving skills and perfectionism scores of sports high school students were above the average. Although no significant results were found in the problem-solving skills sub-dimensions and total scores of sports high school students according to the gender variable, it was found that the averages of female students were higher. Although there was no significant result in the perfectionism sub-dimensions and total scores of sports high school students according to the gender variable, it was found that the averages of female students were higher. Statistically significant differences were obtained in favor of female athlete students in the Criticism from Family dimension of the Frost Multidimensional Perfectionism Scale, and in favor of athlete students involved in team sports in the Not Being Sure About What They Do dimension. It was concluded that there were weak-level relationships between the Perception Scale for Students’ Problem Solving Skills and the Frost Multidimensional Perfectionism Scale sub-dimension scores.